The Influence Of Digital Financial Literacy And Locus Of Control On Financial Satisfaction Mediated By Financial Well-Being Among Generation Z In Jambi City - Ervina Oktavia Rizki; Besse Wediawati; Andang Fazri (Cita konsultindo, 2025)
This study aims to determine the effect of digital financial literacy and locus of control on financial satisfaction, mediated by financial well-being among Generation Z in Jambi City. The study adopts a quantitative approach using the Cochran formula for sampling. The sample in this study amounted to 96 respondents. Data were collected through questionnaires measured on a Likert scale. The data analysis method used was Partial Least Square (PLS), processed using SmartPLS 3.0 software. The results indicate that both digital financial literacy and locus of control have a significant effect on financial satisfaction. Digital financial literacy also has a significant positive effect on financial well-being. However, locus of control does not significantly affect financial well-being. Furthermore, financial well-being mediates the relationship between digital financial literacy and financial satisfaction, but it does not mediate the relationship between locus of control and financial satisfaction.